TUGAS, TANGGUNG JAWAB, DAN KETERLIBATAN WALl BAPTIS DALAM PENDIDIKAN IMAN BAPTISAN DI PAROKI MATER DEI MADIUN - Franciska Triningsih; Cornelius Triwidya Tjahja Utama (Lembaga Penelitian STKIP Widya Yuwana, 2019)
In child baptism sacrament, parents together with the godparents cooperate to religious education of the baptism child, with the purpose of making children being able to grow up in faith. However, in fact, there are some godparents that have not been able to do their tasks and responsibilities and also their involvement in teaching baptism child's faith. Thus, it is become very important to be known about how the godparents understanding on godparents description and also explain the tasks and responsibility also the involvement of the godparents in teaching child's faith. Here is the significant order of godparents which is accompanying baptism child in the process of faith development. This scientific work research is aimed to find out how are the tasks and responsibilities also the involvement of the godparents within the baptism child's faith religious education in mater dei madiun parish. The results of the research indicate that large amount of godparents know the godparents essence from the description, rules and regulations and also tasks and responsibilities of the godparents but not yet deepen. Related to the involvement of the godparents in teaching child's faith can be seen from how the godparents participate in doing what become their tasks and responsibilities while teaching the child and all the godparents declare that he/she have been involved in the child's faith religious education through all short of associations for the baptism child from the baptism preparation, while baptism process up to the end and after the baptism sacrament.